Mast cells in infantile haemangioma possess a primitive myeloid phenotype. Issue 7 (4th April 2013) - Itinteang, Tinte; Tan, Swee T; Jia, Jun; Steel, Ryan; Laing, Emma L; Brasch, Helen D; Day, Darren J
Abstract : Aims: Recent reports on infantile haemangioma (IH) have demonstrated a primitive population of interstitial cells expressing the embryonic transcription factor, Nanog, with decreasing abundance during involution. In this report we investigated the expression of Nanog on mast cells in all three phases of IH progression. Methods: Paraffin-embedded sections of six proliferating, six involuting and six involuted IH lesions were used to investigate the expression of tryptase, Nanog, CD45, CD34 and GLUT-1 by immunostaining. Results: Mast cells, identified by their expression of tryptase, were located in the interstitium of IH lesions. 93%, 42% and 0% of these tryptase + cells also expressed Nanog, in proliferating, involuting and involuted IH, respectively. Conclusions: The identification of an abundant population of tryptase + /Nanog + cells in IH is novel. The relative loss of Nanog expression as IH involutes may be a result of maturation and/or proliferation of these cells. This report supports the primitive nature of IH.